Pendampingan Digitalisasi Berbasis Katalog Museum Alas Trik Desa Kedungbocok Kecamatan Tarik Kabupaten Sidoarjo - Ridlo, Miftakhur Ridlo (Journal of Science and Social Development, 2025)
Alas Trik Museum, Kedungbocok Village, has adopted catalog-based digitization as a step to facilitate public access to its historical collections. With the rapid advancement of digital technology, this change allows museums to overcome some of the limitations of traditional collection management. Catalog-based digitization creates opportunities for museum collections to be widely accessible through the internet, allowing people from various countries to explore and learn about local history and culture without having to physically visit the museum. This paper discusses in detail the implementation of catalog-based digitization at Alas Trik Museum, which not only increases the effectiveness of collection management and presentation, but also opens up new avenues for education and information dissemination. With digitization, historical collections can be presented more engagingly and interactively, fostering a deeper understanding and respect for the cultural and historical values contained therein. However, the process of implementing this digitization also faces various challenges, such as the need for appropriate technological infrastructure, educated human resources, and adaptation to ever-changing technological developments. This article also discusses these challenges and how efforts to overcome them can have a positive impact on the growth of museums and the preservation of cultural heritage. With this discussion, it is hoped that readers can better understand the significance of digitalization in the context of museums and how this innovation can enrich the visitor experience and expand publications on history and culture, so that the Alas Trik Museum remains relevant and contributes to the preservation of culture globally.